Investigation of Magnetic Properties of Poly Vinyl Chloride Composites Prepared Using Different Ratios of Fe2O3 (Maghemite) Nanoparticles - Pekdemir, Mustafa Ersin; Coşkun, Mehmet Fatih (My University, 2022)
Composites were prepared using polyvinyl chloride (PVC) and different percentages of Fe2O3 nanoparticles. All composites were characterized by FT-IR spectroscopy. Then, the thermal properties of the composites prepared in 1% and 10% ratios were examined. It was observed that the initial decomposition temperature (Ti) values of PVC composites prepared with Fe2O3 nanoparticles addition were lower than pure PVC. Magnetic properties of composites were examined with a vibrating sample magnetometer (VSM). The saturation magnetization values of PVC composites prepared by using 1% and 10% Fe2O3 were 2.77 and 7.06 emu / g, respectively.
Keywords: PVC; Fe2O3 Nanoparticle; Magnetization; Maghemite; VSM